2015
DOI: 10.1039/c4bm00385c
|View full text |Cite
|
Sign up to set email alerts
|

Cell membrane-inspired polymeric micelles as carriers for drug delivery

Abstract: In cancer therapy, surface engineering of drug delivery systems plays an essential role in their colloidal stability, biocompatibility and prolonged blood circulation. Inspired by the cell membrane consisting of phospholipids and glycolipids, a zwitterionic phosphorylcholine functionalized chitosan oligosaccharide (PC-CSO) was first synthesized to mimic the hydrophilic head groups of those amphipathic lipids. Then hydrophobic stearic acid (SA) similar to lipid fatty acids was grafted onto PC-CSO to form amphip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…[28][29] As a natural linear polysaccharide, chitosan and its derivatives are widely employed or assessed in biomedical application due to their nontoxic, biocompatible and biodegradable properties. [30][31][32] The rich reactive amino groups of chitosan are useful for chemical modifications. Moreover, it has been reported that chitosan modified nanoparticles could enhance the targeted accumulation and facilitate the tumor uptake due to its positively charged surface.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29] As a natural linear polysaccharide, chitosan and its derivatives are widely employed or assessed in biomedical application due to their nontoxic, biocompatible and biodegradable properties. [30][31][32] The rich reactive amino groups of chitosan are useful for chemical modifications. Moreover, it has been reported that chitosan modified nanoparticles could enhance the targeted accumulation and facilitate the tumor uptake due to its positively charged surface.…”
Section: Introductionmentioning
confidence: 99%
“…To address these dilemmas, micelles as a preferable drug delivery system (DDS) based on various types of polymeric materials have been proposed. 1,2 Micelles have raised a special interest as nano-sized DDSs not only because they provide an increased solubility and stability of hydrophobic drugs, 3,4 but also due to their superior advantages versus the free drug both in vitro and in vivo. 5 Micelles with a size between 20 and 200 nm are large enough to prevent the premature elimination via glomerular ltration and sufficiently small to pass through certain blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…The Au@GO-ZC incorporation with nystatin led to significant decreases in MIP production by 520 and 212 pg mL −1 for An/Am = 0.3 and An/Am = 0.7, respectively. This might be due to binding cell surface receptors by ZC 33 that regulates MIP production by nystatin through modifying cell signaling pathways. Insets of Fig.…”
Section: Resultsmentioning
confidence: 99%